Horizontal Eye Position Affects Measured Vertical VOR Gain on the Video Head Impulse Test - McGarvie, Leigh A.; Martinez-Lopez, Marta; Burgess, Ann M.; MacDougall, Hamish G.; Curthoys, Ian S. (Frontiers in Neurology, 2015)
Background/Hypothesis. With the video Head Impulse Test (vHIT), the vertical VOR gain is defined as (vertical eye velocity/vertical head velocity), but compensatory eye movements to vertical canal stimulation usually have a torsional component. To minimize the contribution of torsion to the eye movement measurement, the horizontal gaze direction should be directed 40º from straight ahead so it is in the plane of the stimulated canal plane pair. Hypothesis: as gaze is systematically moved horizontally away from canal plane alignment, the measured vertical VOR gain should decrease. Study Design. 10 healthy subjects, with vHIT measuring vertical eye movement to head impulses in the plane of the left anterior-right posterior (LARP) canal plane, with gaze at one of 5 horizontal gaze positions (40º (aligned with the LARP plane), 20º, 0º, -20º, -40º). Methods. Every head impulse was in the LARP plane. The compensatory eye movement was measured by the vHIT prototype system. The one operator delivered every impulse. Results. The canal stimulus remained identical across trials, but the measured vertical VOR gain decreased as horizontal gaze angle was shifted away from alignment with the LARP canal plane. Conclusion. In measuring vertical VOR gain with vHIT the horizontal gaze angle should be aligned with the canal plane under test.